Responsibility of Maya World Crimes in Indonesia's Legal System - Henny Saida Flora (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Information and communication technology has changed the behavior of society and human civilization globally. In addition, the development of information technology has caused the world to be indefinitely and cause significant social change to take place so quickly. Information technology is now a double-edged sword, because in addition to contributing to the improvement of welfare, advancement, and human civilization as well as an effective arena of action against the law one of which is cyber crime. In Criminal Law any person who commits a crime, especially a cyber crime, remains to be observed whether the perpetrator may be subject to criminal liability if committing a crime or a violation of a crime. A person who commits a criminal offense may be liable to a crime if it satisfies all elements contained in criminal liability, whereas if the person does not fulfill any of the elements of criminal liability, it can not be punished by any lawsuit. This criminal liability issue is closely related to the error. The entire laws and regulations contained in the Criminal Code as well as the special law outside the Criminal Code, in this case is the Law Number 11 Year 2008 on Information and Electronic Transactions, in essence a unity a punishment system consisting of general rules and special rules. The general rules are contained in the Criminal Code and special rules are contained in the Information and Electronic Transactions Act, all of which will be imposed on the cyber crime if there is an element of criminal responsibility in the perpetrator.